High quality kerfless silicon mono-crystalline wafers and cells by high throughput epitaxial growth. Issue 1666 (21st July 2014) - Hao, R.; Ravi, T.S.; Siva, V.; Vatus, J.; Miller, D.; Custodio, J.; Moyers, K.
ABSTRACT: Crystalline silicon based photovoltaics continues to be the dominant technology for large scale deployment of solar energy. While impressive cost gains in silicon based PV have come with scale, there remains a strong push for increased efficiencies and further lowering of manufacturing costs to achieve true grid parity. So far, however, there has not been a production proven approach that reduces the cost while maintaining or increasing the efficiency. Attempts to reduce the amount of silicon used, for example, have led to development of various kerfless wafer manufacturing approaches. While some of these approaches have shown the potential for reduced costs, they also compromise the efficiency mainly due to the inferior quality of the material. Epitaxy based kerfless silicon wafers, on the other hand, has shown the potential to reverse this trend offering lower manufacturing costs while maintaining or even enhancing the efficiency due to the high quality of the n-type and p-type silicon epitaxial (Epi) wafers. In this work, we present key aspects of Crystal Solar's patented high throughput production silicon epitaxial reactor and its use in the manufacture of standard thickness N and P wafers. Besides the advantage of having significantly reduced cost, these Epi wafers have high quality, better mechanical strength and resistance to light inducted degradation due to significantly reduced oxygen content.